Adapting ruminants to Leucaena toxicity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Ruminants fed leucaena, in Hawaii where the shrub is naturalized, show no toxicity to the alkaloids contained in the plant's foliage, whereas ruminants fed the foliage in countries where the plant has been recently introduced may do so. Assuming...